Piraí digital e a teoria ator-rede: a trajetória de inclusão e desenvolvimento de Piraí - Teles, Adonai (2010)
The city of Piraí, in the state of Rio de Janeiro, Brazil, hosts the program Piraí Digital, a set of initiatives, in five areas - government, education, health, business and citizenship – aimed to bridge the digital divide in the city and contribute to its development. The program was studied through the association between a heuristic model for analysis of digital inclusion and Actor-Network Theory (ANT). This work presents a description of the evolution of the program according to the actors who have built it. Between 1997 and 2009, Piraí Digital contributed to a number of positive changes in Piraí, especially in the areas of education, which adopted the 1:1 computing in its public system in 2009; health care, which uses the city‘s network structure and Internet access to disseminate its systems; and government, where public administration has increased productivity and taxes revenues through the computerization of the administrative machinery. The study of Piraí Digital allows us to understand the importance of the association of artifacts - a computer network, telecenters, Master Plans and others - and people in their efforts to overcome the digital divide and contribute to local development. Exploring the contrast between the strong reputation of Piraí Digital outside the municipality and the little knowledge about the program by the local population, the author makes an analogy with the work of sanitation, almost unknown and invisible to many people, but essential for the population. In Piraí, digital sanitation is ready, with bits gushing from the taps in schools and the health care system profiting from IT to spread its information flow for the benefit of the citizens.